Teachers’ Perception of the Minimum Competency Assessment Instrument (AKM) based on Lynk.id to measure Students’ Scientific Literacy on Solar System Material - Veny Endar Hadi Ayuningtyas; Viyanti; Marina Setyarini (Postgraduate, University of Mataram, 2023)
The aim of my research is to determine science teachers' perceptions of the Link.id-based minimum competency assessment instrument to measure students' scientific literacy on solar system material. The research method used in this research is a mixed method with Sequential Explanatory Design. Data was first collected using a questionnaire and then analyzed using descriptive analysis. This questionnaire was distributed to 36 teachers and 124 junior high school students in Metro City. The research results show that teachers have a positive perception of the use of the Lynk-based Minimum Competency Assessment instrument to measure students' scientific literacy on solar system material. The results of the research show that 67% of teachers have not implemented active learning which leads to developing students' scientific literacy, and 33% of teachers have implemented active learning leading to scientific literacy but have not fully implemented the indicators of scientific literacy. Meanwhile, the level of success in an education does not only look at the learning process, just looking at the 21st century the biggest challenge to the development of competency assessment in Indonesia is no longer relying on individual assessments through the National Examination but see the assessment results continuously. Based on the research results, the level of scientific literacy assessment of students in solar system material is low, this is because students have difficulty applying indicators of scientific literacy. Based on the questions that have been studied, it is known that the questions in the cognitive aspect are still at C1 and C2 levels such as memorizing, explaining, and identifying. As well as based on the questionnaire given that 52% of the assessment is still traditional, namely by using a written formative test and not fully able to take advantage of technological developments. So there is a need for an innovative and effective assessment model so that it can provide measurable, valid and efficient results, one of which is using the Lynk.id platform. Based on the results, it can be concluded that science teacher’s perceptions of the Lynk-based minimum competency assessment instrument can measure aspects of student’ scientific literacy in solar system material.